Childhood divided: child soliders and gang members in the Western imagination - Norton, SE (2020)
In many parts of the world, child soldiers are widely understood as innocent victims in need of international protection, while young gang members are viewed as deviant agents in need of state control and punishment. Yet many young people join these groups for very similar reasons. This thesis asks how these opposing images emerged in the United States and United Kingdom and what might explain their divergence. It first considers what is known about the realities of children who join groups that engage in violence. In doing so, it undermines common assumptions about forced recruitment vs. volunteerism and illustrates how many child soldiers and young gang members are motivated by parallel societal, community, interpersonal, and individual factors. It then traces the ways in which child soldiers and young gang members have been portrayed from the 16th to early 21st centuries, showing how the perception and treatment of these figures has changed drastically over time, shaped and reshaped amidst debates about human nature, changing political and economic realities, and shifting group and state interests. Finally, it explores how laws, government rhetoric, and academic work portray child soldiers and young gang members today (2018- 2020), examining dominant narratives and identifying potential cracks in those frameworks. The analysis ultimately reveals how one society can construct two opposed images of childhood based primarily on adult interests, ideas, and insecurities, as well as how those simplistic constructions can impact the worlds of young people themselves. Overlooking the parallels between child soldiers and young gang members risks not only perpetuating those inaccuracies, but also overlooking broader social, racial, and economic inequalities that at once shape and transcend both figures.